2019
DOI: 10.1038/s41598-019-56064-z
|View full text |Cite
|
Sign up to set email alerts
|

A large self-transmissible resistance plasmid from Nigeria contains genes that ameliorate a carrying cost

Abstract: Antimicrobial resistance is rapidly expanding, in a large part due to mobile genetic elements. We screened 94 fecal fluoroquinolone-resistant Escherichia coli isolates from Nigeria for six plasmid-mediated quinolone resistance (PMQR) genes. Sixteen isolates harbored at least one of the PMQR genes and four were positive for aac-6-Ib-cr. In one strain, aac-6-Ib-cr was mapped to a 125 Kb self-transmissible IncFII plasmid, pMB2, which also bears blaCTX-M-15, seven other functional resistance genes and multiple res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…pMB2 was originally extracted from a commensal Escherichia isolate from Nigeria [ 20 , 21 ]. In the course of functional analyses of fitness loci [ 6 ], we additionally observed that DH5α carrying the pRMKO miniplasmid autoaggregated significantly, particularly under low nutrient conditions. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…pMB2 was originally extracted from a commensal Escherichia isolate from Nigeria [ 20 , 21 ]. In the course of functional analyses of fitness loci [ 6 ], we additionally observed that DH5α carrying the pRMKO miniplasmid autoaggregated significantly, particularly under low nutrient conditions. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains (Table 1 ) were cultured in in Luria broth containing chloramphenicol (30 μg/mL), ampicillin (100 μg/mL), tetracycline (25 μg/mL), or neomycin (50 μg/mL), where required for selection, and maintained at − 70 °C in Luria broth:glycerol 1:1. Plasmid pMB2, originally isolated from an Escherichia isolate in Nigeria [ 6 ], and its derivatives are described in Table 1 .…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations